Research progress in external field intensification of forward osmosis process for water treatment: A critical review. (15th August 2022) - Song, Jialing; Yan, Mengying; Ye, Jingling; Zheng, Shengyang; Ee, Liang Ying; Wang, Zhiwei; Li, Jun; Huang, Manhong
Highlights: The advantages of external field-assisted forward osmosis are emphasized. The alleviating mechanisms of ICP and membrane fouling in external field-assisted forward osmosis are outlined. The development of forward osmosis technology with external field assistance is discussed. New research perspective is provided for the development of forward osmosis technology. Abstract: Forward osmosis (FO) is an emerging permeation-driven membrane technology that manifests advantages of low energy consumption, low operating pressure, and uncomplicated engineering compared to conventional membrane processes. The key issues that need to be addressed in FO are membrane fouling, concentration polarization (CP) and reverse solute diffusion (RSD). They can lead to problems about loss of draw solutes and reduced membrane lifetime, which not only affect the water treatment effectiveness of FO membranes, but also increase the economic cost. Current research has focused on FO membrane preparation and modification strategies, as well as on the selection of draw solutions. Unfortunately, these intrinsic solutions had limited success in unraveling these phenomena. In this paper, we provide a brief review of the current state of research on existing external field-assisted FO systems (including electric-, pressure-, magnetic-, ultrasonic-, light- and flow-assisted FO system), analyze their mitigation mechanisms for the above key problems, and explore potential research directions to aid in the further development of FO systems. This review aims to reveal the feasibility of the development of external field-assisted FO technology to achieve a more economical and efficient FO treatment process. Graphical abstract: Image, graphical abstract